Tahqiq and Takhrij Hadith in the Hadis penting Papadang Ati by Moh. E. Hasim for the Development of Local Hadith Literature in Indonesia - Dadah, Dadah (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
This study examines the development of local hadith literature, particularly the Hadis Penting Papadang Ati Book by Moh. E. Hasim, The primary focus is on the tahqiq and takhrij of hadiths, especially in the chapter on prayer, which contains 256 hadiths, to evaluate the validity and relevance of this work. Using a qualitative method with content analysis, this research explores the author's biography, works, and systematic methodology of the book's composition. The findings indicate that Hasim used Sundanese as the main medium for writing, translating, and explaining hadiths. This approach provides broader access for the local community to understand Islamic teaching. Key findings include the presence of hadiths, supported by numerous corroborations, from complete sources from authoritative books such as Sahih Bukhari and Muslims. However, some hadiths lack complete chains of narration (sanad), necessitating further study to strengthen their authenticity. The novelty of this research lies in analyzing the use of the Sundanese language as a medium of da'wah that connects Islamic teachings with local culture, making the book a relevant spiritual guide. The academic implications highlight the importance of developing locally based hadith literature that considers community needs without compromising scholarly validity. This research recommends further studies in other chapters of Hadis Penting Papadang Ati and a deeper exploration of integrating local traditions with scholarly methodologies in hadith studies